Peran Orang Tua Dalam Mengurangi Kecanggungan Sosial Pada Anak Usia Dini - Ifa Maulida Rambe; Mhd. Fuad Zaini Siregar (Universitas 45 Surabaya, 2023)
This research is motivated by issues in the village of Marbau, namely two shy children aged 5-6 years old. Shyness is considered a normal behavior by some parents. The purpose of this study is to identify and describe the characteristics of shy children, the role of parents in dealing with shy children, and the factors that support and hinder overcoming the role of parents in dealing with shy children. This research uses a descriptive qualitative case study approach, where the research is conducted intensively, in-depth, and attempts to obtain as much information as possible regarding the role of parents in dealing with shy children. Data collected for this research are obtained from events, activities, and behaviors relevant to the research objectives. It is found that children who are the subjects of the study have characteristics such as reluctance to speak, tendency to play alone, lack of openness, difficulty in answering questions, and limited interaction. Parents play a crucial role in helping children overcome their shyness. They need to understand the causes and continue to encourage children's strengths to feel comfortable in socializing. The results of the study emphasize the importance of the role of parents in helping children overcome shyness. This role not only occurs within the family environment but also cannot be replaced by educational institutions. Parents are advised to find out the causes of their children's shyness and continue to encourage their strengths and talents when socializing with new friends. Thus, they can help children feel comfortable and confident in social interaction.